IgG Induced by Vaccination With Ascaris suum Extracts Is Protective Against Infection - Gazzinelli-Guimarães, Ana Clara; Gazzinelli-Guimarães, Pedro Henrique; Nogueira, Denise Silva; Oliveira, Fabrício Marcus Silva; Barbosa, Fernando Sérgio; Amorim, Chiara Cássia Oliveira; Cardoso, Mariana Santos; Kraemer, Lucas; Caliari, Marcelo Vidigal; Akamatsu, Milena Apetito; Ho, Paulo Lee; Jones, Kathryn Marie; et al. (Frontiers in Immunology, 2018)
Human ascariasis has a global and cosmopolitan distribution, and has been characterized as the most prevalent neglected tropical disease worldwide. The development of a preventive vaccine is highly desirable to complement current measures required for this parasitic infection control and to reduce chronic childhood morbidities. In the present study, we describe the mechanism of protection elicited by a preventive vaccine against ascariasis. Vaccine efficacy was evaluated after immunization with three different Ascaris suum antigen extracts formulated with monophosphoryl lipid A (MPLA) as an adjuvant: crude extract of adult worm (ExAD); crude extract of adult worm cuticle (CUT); and crude extract of infective larvae (L3) (ExL3). Immunogenicity elicited by immunization was assessed by measuring antibody responses, cytokine production and influx of tissue inflammatory cells. Vaccine efficacy was evaluated by measuring the reductions in the numbers of larvae in the lungs of immunized BALB/c mice that were challenged with Ascaris suum eggs. Moreover, lung physiology and functionality were tested by spirometry to determine clinical efficacy. Finally, the role of host antibody mediated protection was determined by passive transfer of serum from immunized mice. Significant reductions in the total number of migrating larvae were observed in mice immunized with ExL3 61% (p <0.001), CUT 59% (p <0.001) and ExAD 51% (p <0.01) antigens in comparison with non-immunized mice. For the Ascaris antigen-specific IgG antibody levels, a significant and progressive increase was observed with each round of immunization, in association with a marked increase of IgG1 and IgG3 subclasses. Moreover, a significant increase in concentration of IL-5 and IL-10 (pre-challenge) in the blood and IL-10 in the lung tissue (post-challenge) was induced by CUT immunization. Finally, ExL3 and CUT- immunized mice showed a marked improvement in lung pathology and tissue fibrosis as well as reduced pulmonary dysfunction induced by Ascaris challenge, when compared to non-immunized mice. Moreover, the passive transfer of specific IgG antibodies from ExL3, CUT and ExAD elicited a protective response in naïve mice, with significant reductions in parasite burdens in lungs of 65%, 64% and 64%, respectively. Taken together, these studies indicated that IgG antibodies contribute to protective immunity.